Efforts to Maintain the Existence of Tepak Dance at Sang Putri Sriwijaya Studio - Anggun, Anggun; Wardiah, Dessy; NAD, Nugroho (CV. Rayyan Dwi Bharata, 2023)
Tepak dance is one of the traditional arts originating from the South Sumatra region, especially the city of Palembang, which is one of the artistic treasures in the city of Palembang. This dance is a traditional South Sumatran dance created by Mrs. Sukaina Rojak and Mrs. Tina Hajigong in 1945. The origin of the formation of this tepak dance is taken from the Tanggai Dance movement and also the Gending Sriwijaya Dance, in terms of the movement it is the same but in terms of the lyrics of the song it is different, as time goes by the Tepak Dance undergoes changes or reforms, namely in terms of different floor patterns. The Tanggai dance does not stand up, while the Tepak dance has a standing movement, namely when the Stupa and Borobudur are doing the movement, they stand up and form a straight line. The purpose of this study is to find out and describe efforts to preserve the Tepak Dance in the city of Palembang. The method used in this research is Qualitative Description, with the object of this research is Tepak Dance and the informant in this study is Aunt Lina Muchtar, data collection was carried out by researchers through observation, interviews and documentation. Based on the findings of this study, Palembang residents know about Tepak Dance and its business or existence. Because, until now the Tepak Dance is still often performed at various events since today. Artists and studios have participated in the development of the Tepak dance, including the Sang Putri Palembang studio, and have contributed to the continued existence of the Tepak dance.